Tactile short-term memory for stimuli presented on the fingertips and across the rest of the body surface. - Auvray, M; Gallace, A; Spence, C (2011)
The aim of this study was to investigate the extent to which tactile information that is unavailable for full conscious report can be accessed using partial-report procedures. In Experiment 1, participants reported the total number of tactile stimuli (up to six) presented simultaneously to their fingertips (numerosity judgment task). In another condition, after being presented with the tactile display, they had to detect whether or not the position indicated by a (visual or tactile) probe had previously contained a tactile stimulus (partial-report task). Participants correctly reported up to three stimuli in the numerosity judgment task, but their performance was far better in the partial-report task: Up to six stimuli were perceived at the shortest target-probe intervals. A similar pattern of results was observed when the participants performed a concurrent articulatory suppression task (Exp. 2). The results of a final experiment revealed that performance in the partial-report task was overall better for stimuli presented on the fingertips than for stimuli presented across the rest of the body surface. These results demonstrate that tactile information that is unavailable for report in a numerosity task can nevertheless sometimes still be accessed when a partial-report procedure is used instead.